The effect of scents on alertness - Lim, Ke Hui (2013)
1. To determine if scent helps to increase alertness and wakefulness levels in humans. 2. To investigate how administering scent at intervals will affect alertness levels. 3. To investigate the effect of scent intensity on alertness levels. [2nd Award]